Efeito da inibição da calcineurina pela ciclosporina a em células planctônicas e biofilme de complexo Candida parapsilosis - Macêdo, Ramila de Brito (2013)
Candida parapsilosis Complex comprises three species, C. parapsilosis sensu stricto, C. metapsilosis and C. orthopsilosis, which have the same phenotypic characteristics, can be differentiated only by the genotype using PCR with restriction enzyme. The C. parapsilosis Complex is gaining prominence in the global epidemiology of candidiasis to be the second or third most isolated species, moreover, reports of resistance to some antifungal agents are worrying. Calcineurin molecule also responsible for resistance to antifungal drugs and thinking of new molecular targets with the objective of this study was to evaluate the potential synergistic antifungal and calcineurin inhibitor, cyclosporin A, against planktonic and biofilm forms of strains C. parapsilosis Complex from clinical sources. The susceptility assays with amphotericin B, fluconazole, voriconazole, caspofungin and cyclosporin A were performed by microdilution in accordance with the guidelines of the Clinical Laboratory Standards Institute. The method board in microdilution assay performed tests for synergism against planktonic cells of strains of C. parapsilosis Complex. Antifungal combinations formed by cyclosporin A were evaluated against biofilms forming and mature in polystyrene plates, where differences in the pattern of antifungal susceptibility among species were observed, but strains of C. parapsilosis sensu stricto were more sensitive to cyclosporin A to C. orthopsilosis and C. metapsilosis. Synergism between the antifungal and cyclosporin A was observed in strains of C. parapsilosis Complex. The combinations formed by antifungal and cyclosporin A were able to prevent the growth of the species in the planktonic phase of the complex, as well as in biofilm formation in CIM10X and CIM50X and showed inhibitory effect against mature biofilms of C. parapsilosis sensu stricto, C. metapsilosis and C. orthopsilosis in CIM50X. These results support the potential of inhibiting fungal calcineurin as a promising approach for increasing the efficiency of antifungal drugs.